2012
DOI: 10.1063/1.4736848
|View full text |Cite
|
Sign up to set email alerts
|

A numerical electromagnetic linear dispersion relation for Maxwellian ring-beam velocity distributions

Abstract: A positive slope in a velocity distribution function perpendicular to the ambient magnetic field, such as due to a loss cone or ring velocity distribution, can become a free energy source for the excitation of various plasma waves. Since there exists no analytic expression for integrals of Maxwellian ring velocity distribution functions, their linear properties have previously been studied using several approximations or modeled distributions. In this paper, a numerical method for analyzing the linear dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…The new approach we propose is motivated by the development of a dispersion solver that is based on ring beam velocity distributions (Min & Liu, ; Umeda et al, ), rather than the more conventional multiple bi‐Maxwellian distributions. The dispersion solver of Min and Liu treats particle distributions as a sum of multiple individual ring beam distributions of the form (Umeda et al, ) fj(),vv=njπ3/2θjθj20.5emCjevvitalicdj2/θj2evvitalicrj2/θj2 where j denotes the individual ring beam, v dj is the parallel drift speed of the j th beam, v rj is the radius of the velocity space ring, θ || j and θ ⊥ j characterize the thermal spread of the ring in the directions parallel and perpendicular to the magnetic field, and C j is a constant of the form Cj=evrj2/θj2+π()vrjθj[]1+italicerf()vrjθj …”
Section: Characterization Of Distributionsmentioning
confidence: 99%
“…The new approach we propose is motivated by the development of a dispersion solver that is based on ring beam velocity distributions (Min & Liu, ; Umeda et al, ), rather than the more conventional multiple bi‐Maxwellian distributions. The dispersion solver of Min and Liu treats particle distributions as a sum of multiple individual ring beam distributions of the form (Umeda et al, ) fj(),vv=njπ3/2θjθj20.5emCjevvitalicdj2/θj2evvitalicrj2/θj2 where j denotes the individual ring beam, v dj is the parallel drift speed of the j th beam, v rj is the radius of the velocity space ring, θ || j and θ ⊥ j characterize the thermal spread of the ring in the directions parallel and perpendicular to the magnetic field, and C j is a constant of the form Cj=evrj2/θj2+π()vrjθj[]1+italicerf()vrjθj …”
Section: Characterization Of Distributionsmentioning
confidence: 99%
“…Such distributions provide a positive gradient parallel and perpendicular relative to the magnetic field. Umeda et al [2007Umeda et al [ , 2012 showed that electromagnetic chorus and electron cyclotron harmonic (ECH) waves could be generated by such distributions. Model chorus waves, for example, were unstable in two relatively narrow bands above and below f ce /2, similar to the observed frequency spectra in Figures 2 and 4.…”
Section: 1002/2013gl059165mentioning
confidence: 99%
“…It should be noted that EN emissions are referred to as magnetosonic mode waves (Boardsen et al, ; Gul'elmi et al, ) and Rauch and Roux () referred to this wave as the class‐2 wave. EN emissions are generated through the ring distribution of the ring current protons (Ma et al, ; Min & Liu, ; Umeda et al, ). EN emissions are generated near the magnetic equator (e.g., Boardsen et al, ; Santolik et al, ) and propagate across the magnetic field lines (Ma et al, ).…”
Section: Introductionmentioning
confidence: 99%